Parental involvement in the work of preschool institutions - Маrija R. Marković; Zorica Č. Stanisavljević Petrović; Аnastasija S. Mamutović (University of Belgrade, Teacher Education Faculty, 2020)
Parental involvement in the life and work of the preschool institutions is an issue that is becoming increasingly relevant as the reform of the system of the pre-school education unfolds. With the introduction of The New Preschool Curriculum Framework - Years of Ascent (2018), this matter has become fairly significant, because the new curriculum perceives parents as key partners in achieving the goals of the institutional preschool education. Accordingly, there is a clear need to thoroughly study this topic and examine all relevant factors which determine an active positioning of parents in the process of the preschool education. In that context, it is very important to establish parents´ self-assessment of their involvement in the process of the pre-school education. This paper aims to examine parents´ attitudes towards their involvement in the work of preschool institutions. The paper constitutes a part of a more extensive research which deals with the field of parents´ co-operation with pre-school institutions. In this paper the authors present the results of a subscale that examines parents´ attitudes regarding their involvement in the work of pre-school institutions. The research included 763 parents whose children attend public preschool institutions on the territory of Serbia. The results obtained through the research show that parents believe that they have been adequately included in the work of the preschool institutions and they consider themselves informed and active partners in the process of co-operation. Concerning the independent research variables, the results indicate that mothers are more involved than fathers, as well as that younger parents are more active than those who belong to an older category of parents. The parents´ education level has proven to be an important factor behind parental involvement, as well as the variable relating to a specific education group that children attend. Following the obtained results, one can conclude that parents´ self-assessment regarding their involvement in the work of preschool institutions engenders optimism and it supports the attitude that parental involvement is of immense significance for the quality of the preschool education.